Targeting patients for multimorbid care management interventions: the case for equity in high-risk patient identification - Shadmi, Efrat; Freund, Tobias (International journal for equity in health, 2013)
Targeting patients for multimorbid care management interventions requires accurate and comprehensive assessment of patients’ need in order to direct resources to those who need and can benefit from them the most. Multimorbid patient selection is complicated due to the lack of clear criteria - unlike disease management programs for which patients with a specific condition are identified. This ambiguity can potentially result in inequitable selection, as biases in selection may differentially affect patients from disadvantaged population groups. Patient selection could in principal be performed in three ways: physician referral, patient screening surveys, or by statistical prediction algorithms. This paper discusses equity issues related to each method. We conclude that each method may result in inequitable selection and bias, such as physicians’ attentiveness or familiarity, or prediction models’ reliance on prior resource use, potentially affected by socio-cultural and economic barriers. These biases should be acknowledged and dealt with. We recommend combining patient selection approaches to achieve high care sensitivity, efficiency and equity.